Adiantum spp. Maidenhair Fern - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about the maidenhair fern (Adiantum spp.), a delicate, airy fern native to North America. It thrives in shady, moist environments and is suitable for both outdoor landscapes and indoor settings with bright, indirect light. The fern features light grey-green, soft foliage and is best planted in masses or as ground cover. It requires well-drained soils with high organic matter and does not tolerate dry conditions. The document details its growth habits, soil preferences, and potential pests, highlighting its ornamental value and suitability for various garden settings. Original publication date October 1999.